"What I Want to Do as a Father Is Be There": Constructions of School Involvement for Fathers of Children with Complex Disabilities. (September 2019) - Pancsofar, Nadya; Petroff, Jerry G.; Rao, Shridevi; Mangel, Alyssa
Fathers of children with complex disabilities can play an important role in the development and learning of their children; however, very little is known about their school involvement experiences. We conducted semi-structured interviews with 15 fathers of children with complex disabilities to learn how these fathers perceived their involvement in their children's education and schooling. Fathers constructed their school involvement with a consideration of their work and co-parenting experiences. Their employment was perceived as a form of indirect involvement in their children's education, but could also be associated with barriers to more direct school involvement. Fathers also discussed the role of the co-parenting relationship in their school experiences and identified several factors that contributed to a greater involvement of mothers in school settings. Among these were a perceived unique expertise of mothers and school environments that were more welcoming to mothers. They also discussed some potentially negative ramifications of being less involved in school settings, compared with mothers.